Systematic Investigation of the Diffusion Welding Behavior of the Austenitic Stainless Steel 304 (1.4301). Issue 11 (12th May 2014) - Gietzelt, Thomas; Toth, Volker; Huell, Andreas; Messerschmidt, Florian; Dittmeyer, Roland
<x xml:space="preserve">Abstract</x> The deformation behavior of SS 304 is investigated at three diffusion welding temperatures and different durations. Samples 100 mm in height consisting of five pieces and manufactured from pultrusion round stock are used for studying the diffusion across the bonding planes. The joining cross‐section varies from top to bottom covering bonding pressures from 15 to 25 MPa. From the results, a regression equation is derived allowing the calculation of expected deformation for any other temperature and duration within the investigated range. The approach is validated by an experiment with arbitrary temperature and welding duration. To study the influence of the grain size, orientation and passivation layers, a sample made of 51 sheets, 2 mm in thickness each, is diffusion welded and the results are compared.